EFISIENSI ECENG GONDOK DALAM PENYISIHAN BAHAN ORGANIK PADA LINDI TPA GUNUNG TUGEL PURWOKERTO - Slamet Santoso (Purifikasi, 2010)
Leachate of solid waste disposal site contains organic material in high concentrations. The organic matter in the leachate can be reduced by phytoremediation using water hyacinth (Echhornia crassipes). The aim of this research was to determine the effect of coverage area, residence time, and their interactions in reducing the organic matter concentrations in the leachate. The method was a designed experiment, which was based on Completely Randomized Design (CRD) with Factorial Design. The first factor was the percentage of water hyacinth coverage area of 0; 25; 50; 75 and 100%, and the second factor was the length of residence time of 4, 5 and 6 days. Results of this research showed that the coverage area of 75% could remove the BOD and TSS levels up to 53.812 and 62.84% respectively. The coverage area of 100% showed COD removal efficiency of 29.215%, which was the highest when compared to the other variations. The residence time of 6 days was able to reduce the BOD, COD and TSS levels in the highest efficiencies of 49.44; 29.94 and 47.84%. respectively. The combined coverage area of 75% and residence time of 6 days showed the highest BOD and TSS removal efficiencies of 59.19 and 65.14% respectively. Whereas the combined coverage area of 100% and residence time of 5 day system was able to reduce the COD level up to 30.66%.